2012
DOI: 10.3168/jds.2011-4418
|View full text |Cite
|
Sign up to set email alerts
|

Increased fertility in lactating dairy cows resynchronized with Double-Ovsynch compared with Ovsynch initiated 32 d after timed artificial insemination

Abstract: The objective was to determine if using a Double-Ovsynch protocol [DO; Pre-Resynch: GnRH-7 d-PGF(2α)-3 d-GnRH, 7 d later Breeding-Resynch: GnRH-7 d-PGF(2α)-56 h-GnRH-16 h-timed artificial insemination (TAI)] to resynchronize ovulation after a previous TAI would increase synchrony and pregnancies per AI (P/AI) compared with an Ovsynch protocol initiated 32 d after TAI (D32; GnRH-7 d-PGF(2α)-56 h-GnRH-16 h-TAI). Lactating Holstein cows at various days in milk and prior AI services were blocked by parity and rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
137
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(162 citation statements)
references
References 43 publications
(83 reference statements)
17
137
4
2
Order By: Relevance
“…A particularly surprising result from this study was that all of the effect of hCG on fertility was due to a dramatic increase in primiparous cows (39.5%; 215/544 Control primiparous; 49.7%; 266/535 hCG-treated primiparous) with no change due to hCG treatment in multiparous cows (36.0%; 351/975 Control multiparous; 35.7%; 330/925 hCG-treated multiparous). Numerous other studies have reported that first parity cows generally have higher fertility than older cows particularly when cows are bred after protocols that provide excellent synchrony of ovulation for fixed time AI Souza et al, 2008;Giordano et al, 2012b). However, our experiment does not provide a clear explanation for the differences between parities in the fertility effects of hCG.…”
Section: Importance Of High P4 After Aicontrasting
confidence: 62%
See 4 more Smart Citations
“…A particularly surprising result from this study was that all of the effect of hCG on fertility was due to a dramatic increase in primiparous cows (39.5%; 215/544 Control primiparous; 49.7%; 266/535 hCG-treated primiparous) with no change due to hCG treatment in multiparous cows (36.0%; 351/975 Control multiparous; 35.7%; 330/925 hCG-treated multiparous). Numerous other studies have reported that first parity cows generally have higher fertility than older cows particularly when cows are bred after protocols that provide excellent synchrony of ovulation for fixed time AI Souza et al, 2008;Giordano et al, 2012b). However, our experiment does not provide a clear explanation for the differences between parities in the fertility effects of hCG.…”
Section: Importance Of High P4 After Aicontrasting
confidence: 62%
“…Similar to the first study, cows ovulating a follicle of the second follicular wave (high P4 concentrations) had greater P/AI that cows ovulating the first follicular wave (low P4) (41.7% v. 30.4%) (Bisinotto et al, 2010a). Other studies have also reported that low P4 at the beginning of the Ovsynch protocol results in decreased P/AI compared with cows with high P4 concentrations Denicol et al, 2012;Giordano et al, 2012aGiordano et al, , 2012bGiordano et al, and 2013a. In addition, a recent study (Bisinotto et al, 2013) compared cows with a CL at the initiation of a synchronized ovulation program to cows either without a CL, that were untreated, or cows without a CL that were treated with two intravaginal P4 implants (two CIDRs).…”
Section: Fertility In Dairy Cowssupporting
confidence: 60%
See 3 more Smart Citations